Optimization of extraction of lipid from Isochrysis galbana microalgae species for biodiesel synthesis - Silitonga A.S.; Masjuki H.H.; Ong H.C.; Mahlia T.M.I.; Kusumo F. (Taylor and Francis Inc., 2023)
Algae; Biodiesel; Calorific value; Extraction; Genetic engineering; Microorganisms; Palmitic acid; Positive ions; Surface properties; Alternative energy; Biodiesel production; Biodiesel properties; Biodiesel synthesis; Future applications; Higher heating value; Isochrysis galbana; Response surface methodology; Synthetic fuels